Óleos essenciais no controle do fungo Sclerotinia sclerotiorum (LIB.) de Bary in vitro - Siega, Thayllane de Campos (2018)
Sclerotinia sclerotiorum is a fungus that causes the disease known as white stem rot or white mold. Due to the survival capacity of the fungus in the soil through specialized structures called sclerotia and the environmental conditions favorable to its germination, it is indispensable to use integrated measures considering the chemical control and cultural management in its control. The goal of this work was to verify the treatment (volatile and treated efects) of sclerotia with 17 different essential oils, on the myceliogenic and carpogenic germination of S. sclerotiorum, as well as to evaluate in a more specialized way the oils of Melaleuca alternifolia, Eugenia uniflora and Casearia sylvestris in the face of possible morphological changes in the hyphae through the use of scanning electron microscopy (SEM), optical microscopy (OM) and gas chromatography coupled to mass spectrometry (GC/MS). Myceliogenic germination was done in PDA medium and incubation in a BOD type growth chamber at 18 C and 12 hour photoperiod. The essential oils (15 ml/mL) were applied on autoclaved filter paper (1 cm2), attached to the top lid of the Petri R plate, and sclerotia in the center of the PDA - containing plate. For the treated effect with 15 ml/ml + 2 ml of water and 1 drop of Tween R for 2 minutes, arranged in the same manner as the volatile treatment. Germination assays were performed at 24, 48, 72 and 96 hours after the start of incubation. Carpogenic germination was induced in sterilized conditioned soil in Gerbox R and incubation in a growth chamber with a temperature of 18 °C °2 °C, 12 hour photoperiod and soil moisture at 100% field capacity, using dosage of 30 ml/ml essential oil on volatile effect on filter paper for 15 sclerotia and treated effect with 30 ml/ml + 2 ml of water and 1 drop of Tween R for 2 minutes for 60 sclerotia. The experimental design for the two experiments was the completely randomized with four replicates per treatment. The chromatographic analyzes were performed by Embrapa Floresta using automatic injection. The images were taken on the Hitachi TM 3000 scanning electron microscope, operating at 15 kV, with magnifications of 200, 800 and 1000x on Zeiss optical microscope Primo Star model, coupled with Axiocam 105 color camera and the software Zen 2.0 lite (blue edition) the images of the structures of the fungus were carried out. The production of extracellular enzymes from the fungus was also performed, for anda amilase, protease, celulase e esterase. It is concluded that the 17 essential oils used in this study have potential control of the fungus S. sclerotiorum, and it is suggested that the fungicidal action of these essential oils may be linked to its major components, causing an aggressive stimulus in the structures of the fungus, in this way the cells broke their homeostatic equilibrium and undergo a regressive process that can leading to cell death.